Luigi Nono e il cinema: un'arte di Lotta e Fedele alla verità - Calabretto, Roberto (Lucca Libreria Musicale Italiana, 2017)
Nono was not a film composer, in the literal sense of the term: he is therefore not a 'cinematographer', like so many other post-World War II musicians who dedicated themselves to the world of moving images as their main vocation. Nor is he a musician who occasionally collaborated with some director on certain films. Rather, he is a composer who has allowed his music to be used in certain documentaries; who has shown great competence whenever he has had to talk about cinema; who has thought of cinema as a possible moment of inspiration for his own music; and who has made a musical translation of a film he particularly loved, Tarkovsky's Sacrifice. It is precisely by following these paths that we will try to trace our own trajectory, taking up the invitation that Veniero Rizzardi launched in one of his notes in which he wrote: "And yet Nono and the cinema could be a missed chapter in his artistic biography, studded, in this sense, more than anything else, with desiderata, hypotheses, attempts, uncertainties, and many possibilities". (Translated with Deepl.com)
This book studies the influence of film on the music of the great 20th century Italian composer Nono. With indices, a works list, and filmography. Music examples. Figures.
Keywords: Nono, Luigi -- 1924-1990; 20th Century (1901-2000); Film; Music history